2022
DOI: 10.3389/fevo.2022.826910
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Amphibians Vulnerability to Climate Change in China

Abstract: Global climate change is considered to be one of the main threats to organisms. As poikilothermic animals, amphibians are in particular sensitive because they cannot adapt to the dramatic climate change through active physiological regulation. Using 104 representative species, the present study conducted an assessment of amphibians vulnerability to climate change in China through the combination of two approaches. Specifically, 18 vulnerability criteria belonging to five categories (i.e., thermal tolerance, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…Other studies of Chinese vertebrates, mostly amphibians and birds, have shown that threatened species and endemic species are more vulnerable to climate change (Wu, 2020;Luo et al, 2021). Our results show that species currently listed as threatened by the IUCN might have an increased risk of extinction in the future, which is similar to the results of Li et al (2013), and requires immediate conservation planning (Li et al, 2013;Zhao et al, 2022). Generally, our results show that while some species' distribution ranges will increase, a greater number will be severely endangered due to the shrinking of suitable areas and the loss of currently suitable habitats (Li et al, 2013;Wu, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…Other studies of Chinese vertebrates, mostly amphibians and birds, have shown that threatened species and endemic species are more vulnerable to climate change (Wu, 2020;Luo et al, 2021). Our results show that species currently listed as threatened by the IUCN might have an increased risk of extinction in the future, which is similar to the results of Li et al (2013), and requires immediate conservation planning (Li et al, 2013;Zhao et al, 2022). Generally, our results show that while some species' distribution ranges will increase, a greater number will be severely endangered due to the shrinking of suitable areas and the loss of currently suitable habitats (Li et al, 2013;Wu, 2020).…”
Section: Discussionsupporting
confidence: 77%
“…The trend of new species description sometimes misleads the policymakers on amphibian conservation issues. It is already evident that amphibians across the world are facing immense conservation challenges from diverse factors, including climate change, temperature fluctuation ( Grimm et al, 2008 ; Dawson et al, 2011 ; Li, Cohen & Rohr, 2013 ; Rahman, 2014 ; Zhao et al, 2022 ), emerging infectious diseases ( Grant et al, 2016 ; Cohen et al, 2018 ; Scheele et al, 2019 ), invasive species ( Nunes et al, 2019 ; Falaschi et al, 2020 ; Park et al, 2022 ), and habitat alteration ( Cushman, 2006 ; Becker et al, 2007 ; Decena et al, 2020 ). Additionally, the unique characteristics of amphibians make them susceptible to declining risks from both aquatic and terrestrial ecosystems while also enabling them to thrive in both environments ( Becker & Loyola, 2007 ).…”
Section: Introductionmentioning
confidence: 99%